Réponses

Meilleure réponse !
2014-06-16T14:00:24+02:00
Développer :
A=(2x-3)(5-x)+(2x-3)²
A=(10x-2x²-15+3x)+(4x²-12x+9)
A=4x²-2x²+10x+3x-12x-15+9
A=2x²+x-6

Factoriser
A=(2x-3)(5-x)+(2x-3)²
A=(2x-3)[(5-x)+(2x-3)]
A=(2x-3)(5-x+2x-3)
A=(2x-3)(x+2)
  • Utilisateur Brainly
2014-06-16T14:06:35+02:00
Développer : 

=(2x-3)(5-x)+(2x-3)^2 \\ =10x-2x^2-15+3x+4x^2-12x+9 \\ =2x^2+x-6

Factoriser :

=(2x-3)(5-x)+(2x-3)^2 \\ =(2x-3)(5-x)+(2x-3)(2x-3) \\ =(2x-3)(5-x+2x-3) \\ =(2x-3)(x+2)

Bonne journée à toi! =)